High-fat diet fuels prostate cancer progression by rewiring the metabolome and amplifying the MYC program - Labbé, David P.; Zadra, Giorgia; Yang, Meng; Reyes, Jaime M.; Lin, Charles Y.; Cacciatore, Stefano; Ebot, Ericka M.; Creech, Amanda L.; Giunchi, Francesca; Fiorentino, Michelangelo; Elfandy, Habiba; Syamala, Sudeepa; et al. (Nature communications, 2019)
Systemic metabolic alterations associated with increased consumption of saturated fat and obesity are linked with increased risk of prostate cancer progression and mortality, but the molecular underpinnings of this association are poorly understood. Here, we demonstrate in a murine prostate cancer model, that high-fat diet (HFD) enhances the MYC transcriptional program through metabolic alterations that favour histone H4K20 hypomethylation at the promoter regions of MYC regulated genes, leading to increased cellular proliferation and tumour burden. Saturated fat intake (SFI) is also associated with an enhanced MYC transcriptional signature in prostate cancer patients. The SFI-induced MYC signature independently predicts prostate cancer progression and death. Finally, switching from a high-fat to a low-fat diet, attenuates the MYC transcriptional program in mice. Our findings suggest that in primary prostate cancer, dietary SFI contributes to tumour progression by mimicking MYC over expression, setting the stage for therapeutic approaches involving changes to the diet. Prostate cancer progression may be enhanced by a high-fat diet. Here the authors show that a diet high in saturated fats enhance the MYC-driven transcriptional program, a feature that independently predicts prostate cancer progression and death.